Public Sector Asset Management in the Republic of North Macedonia - Dionisijev, Ivan; Roje, Gorana (Center of Excellence in Finance (CEF), 2021)
The successful development of economies depends on effective and efficient public administration. For an effective and efficient public administration, the assets available are of great importance, as governments are responsible for providing high-quality public services to citizens and thus also for managing public sector assets. A clear range of strategic policies set by the government in the process of managing public sector assets leads to efficient and effective public management, which in turn increases the quality of services and improves the lives of citizens. This paper examines how public sector assets are managed in the Republic of North Macedonia, by focusing on both the institutional and organizational aspect and the accounting and financial reporting aspect of public asset management reforms. Both aspects are examined using the qualitative research method (reviewing relevant institutional and non-institutional documents) and supported by survey-based empirical data. The paper also addresses Public Sector Asset Management (PSAM) perspectives and challenges ahead of the Republic of North Macedonia and a clear need to maintain the momentum for continuous improvement (i.e. capacity development efforts) in this area.
This paper is a result of the project Public Accountants Certification Training in North Macedonia (PACT NMAC 3), financially supported by the Ministry of Foreign Affairs of Slovenia. This research is also the result of the international scientific project titled “Challenges of financial and non-financial reporting by public sector entities in the changing user needs environment”, under the classification HRZZ – PZS – 2019 – 02 – 5372. Any opinions, findings, and conclusions or recommendations expressed here are those of the authors and do not necessarily reflect the views of authors’ institutions, the Center of Excellence in Finance or third parties.
Keywords: public sector, asset management, accounting, state audit, North Macedonia